2003
DOI: 10.1002/jbm.b.10072
|View full text |Cite
|
Sign up to set email alerts
|

Migration of polyethylene debris along well‐fixed cemented implants

Abstract: Implants, consisting of smooth Inox cylinders, were cemented into the lower femur and upper tibia of nine sheep to study the distal migration of polyethylene particles. Some implants had a titanium-bead porous coat at the proximal end. These were of three types: In the first type, the porous coat was covered with hydroxyapatite to obtain a bony seal; the second type was prepared for a polymethylmethacrylate seal; in the third type, the porous zone was surrounded by a 2-mm-thick space to allow the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…We examined regions at the interface between PMMA cement and bone, and distal (>5 mm) to the interface (Figure 3). As has been reported by other groups [10, 12, 14, 23], the morphology of these particles included filaments and lenticular shapes, which were visible as individual particles or in clumps (Figure 4A–C). Due to the thickness of the sections, particles that appeared smaller or rounder may have been oriented out of plane.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…We examined regions at the interface between PMMA cement and bone, and distal (>5 mm) to the interface (Figure 3). As has been reported by other groups [10, 12, 14, 23], the morphology of these particles included filaments and lenticular shapes, which were visible as individual particles or in clumps (Figure 4A–C). Due to the thickness of the sections, particles that appeared smaller or rounder may have been oriented out of plane.…”
Section: Resultssupporting
confidence: 82%
“…In comparison to our study, Massin et al [12] examined postmortem retrieved THA femoral components, using polarized light microscopy to identify PE wear debris at both the metal-cement and cement-bone interfaces. They too found birefringent debris within marrow-filled trabecular structures adjacent to the implant, and additionally demonstrated a “reservoir” of debris distal to the component, but remarked on the lack of published material demonstrating distal osteolysis in THA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Massin and colleagues 29 showed that polyethylene particles can migrate around nonloosened cemented femoral components to the distal end of the mantle and suggested that they progress through porosity in cancellous bone. Particles might also move along the interface, aided by fluid motion upon loading.…”
Section: Discussionmentioning
confidence: 99%
“…The fluid may contain wear debris from the articulating surfaces which become lodged in this space and is associated with osteolysis [124]. There is evidence from histological analysis of retrieved implants that the cancellous bone may be part of the effective joint space despite a well-fixed implant [247,248]. Polyethylene has also been observed in the most proximal regions of cemented hips in the bone-cement interface [25].…”
Section: Wear Particles and Metal Ionsmentioning
confidence: 96%